Group-oriented values, rules and cooperation - Ke-young Chu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2004)
This paper uses a game-theoretic framework to explain how collectivist values hamper societies' efforts to elicit cooperation in inter-group games of prisoners' dilemma (PD) and draws on the results of the analysis to interpret the meanings of three historical institutional reform episodes. Group-oriented values, widespread throughout non-western civilizations, can contribute to social cohesion, but tend to cause inter-group conflicts within a country. Regional, ethnic, and other internally cohesive groups often cannot get out of defection traps in political and economic PD games they play with each other. Repeating to play the games enhances chances for, but does not assure, cooperation between these groups. Factionalism makes it more difficult for group-oriented societies, compared with individualist ones, to achieve inter-group cooperation. History shows, however, that some societies have tamed factionalism by reforming their institutions. The institutional reforms in ancient Athens, colonial America, and Singapore show that hybrid political groups, or institutionally-engineered political siblings, which drew their members from rival groups, sought broader social interests than the ethnic or other pre-reform special-interest groups had done, thus, helping the societies achieve Paretian improvements. Indirect democracy in which the representatives of the hybrid political groups were key game players in political processes reduced chances for special-interest groups to form powerful factional coalitions. – collectivism ; cooperation ; economic development ; game theory ; individualism ; institutions ; conflicts
Keywords: C72; D74; O17; H10; 330; Entwicklung; Interessengruppentheorie; Nichtkooperatives Spiel